Estimated pulse wave velocity and cardiovascular events in Chinese - Ji, Chunpeng; Gao, Jingli; Huang, Zhe; Chen, Shuohua; Wang, Guodong; Wu, Shouling; Jonas, Jost B. (International journal of cardiology hypertension, 2020)
The estimated pulse-wave velocity (ePWV) as measure for arterial wall stiffness is associated with an increased risk of cardiovascular disease (CVDs) and all-cause death in Western populations. We investigated the association between ePWV and the incidence of CVDs (myocardial infarction, cerebral infarction, cerebral hemorrhage) and all-cause death in Chinese. The community-based longitudinal Kailuan Study included 98,348 participants undergoing biennial clinical examinations. During a mean follow-up of 10.32 ± 2.14 years, 6967 CVD events (myocardial infarction, n = 1610; cerebral infarction, n = 4634; cerebral hemorrhage, n = 1071) and 9780 all-cause deaths occurred. Stratified by age, sex and presence of cardiovascular risk factors, the incidence of CVDs and all-cause death were higher (P < 0.01) in individuals with ePWV values ≥ 10 m/s than in those with ePWV values < 10 m/s. After adjusting for age, age squared and other conventional cardiovascular risk factors, an ePWV value of ≥10 m/s or each ePWV increase by 1 m/s increased (P < 0.01) the risk for CVDs by 32% (Hazard ratio (HR):1.32; 95% confidence interval (CI):1.23-1.42) and 22% (HR:1.22; 95%CI:1.18-1.27), respectively, and increased the risk for all-cause death significantly (P < 0.01) by 28% (HR:1.28; 95%CI:1.20-1.37) and 10% (HR:1.10; 95%CI:1.07-1.13), respectively. The mean brachial-ankle PWV, measured in 43,208 individuals, was 15.30 ± 3.51 cm/s, with a mean difference of 6.45 m/s (95% limits of agreement:1.24-11.7) to the ePWV. Independently of cardiovascular risk factors, ePWV was associated with CVDs and all-cause mortality in Chinese.
Online verfügbar ab 11. November 2020
Gesehen am 16.10.2024